Coupled systems theory, models, and applications in engineering - Geiser, Juergen (Chapman & Hall/CRC numerical analysis and scientific computing, 2014)
The book discusses the effectiveness, simplicity, stability, and consistency of the methods in solving problems that occur in real-life engineering tasks. It shows how MATLAB® and Simulink® are used to implement the methods. The author also covers the coupling of separate, multiple, and logical scales in applications, including microscale, macroscale, multiscale, and multiphysics problems.